Economics of Johne’s disease control decisions in western Canadian cow-calf herds - Rosengren, Leigh (Kansas State University, 2021)
Johne’s is a chronic and untreatable contagious disease of cattle leading to severe diarrhea, emaciation and eventually death. Nursing calves are susceptible to infection if exposed to shedding cattle or a contaminated environment. The prevalence of Johne’s disease in western Canadian beef herds is currently low, but rising, leaving the industry with a closing opportunity to develop strategies to control this costly disease. The expected returns from consistently applied test and control strategies were evaluated by applying a net present value (NPV) model to outputs from a dynamic disease simulation model. A total of fourteen scenarios were considered with combinations of the initial disease prevalence (0%, 1.5%, and 7%), breeding cow replacement strategy (internal heifer retention or external mature cow purchases) and testing choices (no testing, annual testing with a fictious perfectly sensitive and specific test, and annual testing with a commercially available ELISA blood test). Each scenario was simulated 1000 times for ten years. All models assumed clinical cows were culled. Livestock sales and operating input expenses were used to calculate annual revenues and expenses using a partial budget approach. Year end cash positions were discounted by 7.5% to estimate a NPV for each herd. The distributions of NPVs within scenarios were compared to identify preferred control strategies. Regardless of the initial prevalence of Johne’s disease, the most profitable strategy in infected herds was to purchase external mature replacement cows and conduct no testing. All scenarios with internal replacement heifers had substantially lower NPVs than the comparable strategy with external mature replacements. Scenarios exploring internal heifer replacement strategies led to rising rates of Johne’s infection with those with external breeding stock purchases were able to decrease the disease pressure to a low rate. The most important outcome from this study is that cow-calf operations in western Canada can economically control Johne’s disease through early, consistent culling of clinical animals provided these animals are replaced with cows that have a low rate of Johne’s infection. This project was undertaken because the prevalence of Johne’s positive herds is rising in Saskatchewan and the disease is present in both commercial and seedstock operations. The Saskatchewan Stock Growers Association has managed a surveillance and control program with funding from the Saskatchewan Ministry of Agriculture. This research will help to ensure this surveillance investment has maximum effect.
Keywords: Johne's disease; Canada; Cow-calf herds; Disease control; Agribusiness